Pengaruh Pemanfaatan E-Commerce Terhadap Pendapatan UMKM Di Kota Probolinggo Jawa Timur - Yudi Purwanto; Budi Wahono; Ratna Tri Hardaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This research was conducted to determine the effect of the use of e-commerce on the income of SMEs in Probolinggo City, East Java. This research belongs to the type of explanatory research with a quantitative approach, which was conducted to examine the effect between variables. The population in this study is MSMEs in Probolinggo City. From this population a sample will be determined using the formula method of Slovin so that a sample of 99 samples is obtained. Data analysis in this study consisted of instrument testing, classical assumption test, multiple linear regression analysis, hypothesis testing, and coefficient of determination test.The results of this study indicate that based on the results of the t test there is an influence between the variables of e-commerce utilization on the income variable of MSMEs in Probolinggo City. R Square of 17.3% to the dependent variable, namely MSME income (Y) can be explained by the variable of e-commerce utilization (X) while 82.7% is explained by other variables outside the research model. Keywords: UMKM Income, Utilization of E-Commerce